A systematic review on psychological factors influencing mobile phone addiction among youth in the United States of America - Fadzil, Mohd. Fauzi; Ahmad Ghazali, Akmar Hayati (Human Resource Management Academic Research Society, 2022)
Mobile phone addiction has become one of the main issues affecting the youth of today especially in the United States of America. There are limited systematic review articles on social perspectives of mobile phone addiction among youth and this gears the present article to analyse the existing literature in a systematic way, focusing on youth in the United States of America. This study is guided by PRISMA Statement (Preferred Reporting Items for Systematic reviews and Meta-Analyses) as it offers several advantages. Based on the systematic review on Scopus and Web of Science, a total of 20 out of 83 related articles were selected. Review of these articles resulted in six main themes, namely entertainment, attachment feeling, media platform, safety, friendly technology and internet. These six themes further produced a total of 13 sub-themes. Future studies are recommended to place their focus on a mixed method approach and try to involve expert on validating themes (analysis) of the study. As a conclusion, it’s important for developing country such as Malaysia to study social trends of developing country such as the United States of America because the impact soon or later will be faced by a developing country.